2004
DOI: 10.1021/la048478u
|View full text |Cite
|
Sign up to set email alerts
|

Silver-Colloid-Nucleated Cytochrome c Superstructures Encapsulated in Silica Nanoarchitectures

Abstract: We recently discovered that self-organized superstructures of the heme protein cytochrome c (cyt. c) are nucleated in buffer by gold nanoparticles. The protein molecules within the superstructure survive both silica sol-gel encapsulation and drying from supercritical carbon dioxide to form air-filled biocomposite aerogels that exhibit gas-phase binding activity for nitric oxide. In this investigation, we report that viable proteins are present in biocomposite aerogels when the nucleating metal nanoparticle is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 22 publications
0
49
0
Order By: Relevance
“…Franzen, Feldheim, and coworkers [45] also found that adsorption of a peptide-modified BSA does not saturate with increasing protein concentration, which indicates that more than a monolayer of protein is adsorbing to the nanoparticles. Extensive protein multilayers have been observed previously for cytochrome c on Ag nanoparticles, although these structures were observed under special circumstances including aerogel formation, which may have stabilized their formation [52,53].…”
Section: Quantification Of Bound Hrp and F-hrpmentioning
confidence: 75%
“…Franzen, Feldheim, and coworkers [45] also found that adsorption of a peptide-modified BSA does not saturate with increasing protein concentration, which indicates that more than a monolayer of protein is adsorbing to the nanoparticles. Extensive protein multilayers have been observed previously for cytochrome c on Ag nanoparticles, although these structures were observed under special circumstances including aerogel formation, which may have stabilized their formation [52,53].…”
Section: Quantification Of Bound Hrp and F-hrpmentioning
confidence: 75%
“…This work showed that the defect density of SAMs on the gold substrates created from NP films can have a significant impact in how those SAMs can be used or how they perform in a specific application like protein monolayer electrochemistry where it can impact the signal-to-background of the voltammetry. By better understanding the properties of SAMs that form on the NP-based gold, one can begin to engineer these methods for application to three-dimensional or porous materials applications [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…22 Citrate-capped palladium nanoparticles have only recently been reported in the literature because palladium is an unstable system when compared with other precious metal catalysts like gold and platinum, and tends to agglomerate with other nanoparticles into larger particles. 21 The following optimized protocol is the result of a series of attempts to produce stable palladium nanoparticles.…”
Section: Palladium Synthesismentioning
confidence: 99%